Parables of Enoch : a paradigm shift - Charlesworth, James H.; Bock, Darrell L. (London ; New York : Bloomsbury, 2013)
An interdisciplinary study of the state of the current debate surrounding the 'Parables of Enoch' with regard to their dating, as well as their Jewish character and their potential contribution to aspects of early Christian thought.
Foreword / James H. Charlesworth -- Preface: The books of Enoch: status quaestionis / James H. Charlesworth -- The Son of Man debate revisited (1960-2012) / Geza A. Vermes -- The Son of Man in Mark / James D.G. Dunn -- The date and provenience of the Parables of Enoch / James H. Charlesworth -- Dating the Parables of Enoch: a Forschungsbericht / Darrell L. Bock -- Aramaic and Greek representations of the "Son of Man" and the importance of the Parables of Enoch / Paul Owen -- Moses and Enoch in Second Temple Jewish texts / James VanderKam and Dulcinea Boesenberg -- The book of Enoch and the Galilean archaeology and landscape / Mordechai Aviam -- Did Jesus know the traditions in the Parables of Enoch? / James H. Charlesworth -- Matthew and the Parables of Enoch / Grant Macaskill -- The Parables of Enoch and the synoptic gospels / Leslie Walck -- The Parables of Enoch and the Johannine Son of Man / Francis J. Moloney -- The Enochic Son of Man and the apocalyptic background of the Son of Man sayings in John's gospel / Benjamin E. Reynolds -- The building blocks for Enoch as the Son of Man in the early Enoch tradition / Loren T. Stuckenbruck -- The Parables of Enoch in early Christianity / Lee Martin McDonald -- Conclusion / James H. Charlesworth and Darrell L. Bock -- Select bibliography on "the Son of Man" and the Parables of Enoch: the fruits of 500 years of research devoted to early Jewish texts / James H. Charlesworth -- Concerning the select bibliography / Blake A. Jurgens.
Includes bibliographical references (pages 373-390) and index.
Keywords: Ethiopic book of Enoch -- Criticism, interpretation, etc; Ethiopic book of Enoch -- Parables; Son of Man